Patriotic information systems - Loendorf, Todd; Garson, G. David (1 online resource (xi, 258 pages) illustrations, 2008)
"This book discusses how, with its non-participatory enforcement ethos, its inherent bias against freedom of information, and its massive claims on IT budget resources, the information technology security system of the future may be even less hospitable to the democratic visions which some theorists once anticipated would be among the most important contributions of information technology to society"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Computer security -- Law and legislation -- United States; Data protection -- Law and legislation -- United States; Information technology -- Security measures -- United States; Electronic surveillance -- United States; Public records -- Access control -- United States; Freedom of information -- United States; Privacy, Right of -- United States; Electronic books